2015
DOI: 10.1093/molehr/gav034
|View full text |Cite
|
Sign up to set email alerts
|

Functional disparity between human PAWP and PLCζ in the generation of Ca2+oscillations for oocyte activation

Abstract: Mammalian oocyte activation is mediated by cytosolic calcium (Ca(2+)) oscillations initiated upon delivery of a putative 'sperm factor' by the fertilizing sperm. Previous studies suggest the identity of this sperm factor as the testis-specific phospholipase C-zeta (PLCζ). Recently, a post-acrosomal sheath WW domain-binding protein (PAWP) has been proposed as an alternative sperm factor candidate, following a report that human PAWP protein and cRNA elicited Ca(2+) oscillations in mouse and human oocytes. Those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Among these factors, PLCf has emerged as the strongest candidate and several studies have shown the correlation between absence or deficiency of PLCf with failed fertilization in globozoospermic men (Heytens et al, 2009;and Aghajanpour et al, 2011). However, a growing body of evidence has challenged the importance of PLCf as the key SOAF and proposed other candidate proteins, particularly PAWP and TR-KIT, as the major SOAFs (Muciaccia et al, 2010;Aarabi et al, 2014b;Amdani et al, 2015;Nomikos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, PLCf has emerged as the strongest candidate and several studies have shown the correlation between absence or deficiency of PLCf with failed fertilization in globozoospermic men (Heytens et al, 2009;and Aghajanpour et al, 2011). However, a growing body of evidence has challenged the importance of PLCf as the key SOAF and proposed other candidate proteins, particularly PAWP and TR-KIT, as the major SOAFs (Muciaccia et al, 2010;Aarabi et al, 2014b;Amdani et al, 2015;Nomikos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PAWP protein from injected RNA was validated in these experiment with tagged or untagged RNA, and the levels that were similar or greater than those levels reported to be found in sperm (Wu et al 2007). In addition, injecting the same PY-containing peptide (used by Aarabi et al) into eggs did not result in any inhibition of Ca 2+ i oscillations induced by IVF or ICSI (Nomikos et al 2015a). Thirdly, it has now been shown that PAWP null male mice are fertile and produce sperm that can trigger a normal pattern of Ca 2+ i oscillations and embryonic development after ICSI (Satouh et al 2015).…”
Section: Pawp Is Not Relevant To Egg Activationmentioning
confidence: 82%
“…SOAF activity is present in the perinuclear extracts of the mouse sperm and such extracts were shown to contain several different proteins as well as PLCζ, but these extracts did not contain PAWP (Fujimoto et al 2004). Secondly, in marked contrast to PLCζ, the data showing PAWP's ability to cause Ca 2+ i increases have not been reproducible (Nomikos et al 2014(Nomikos et al , 2015a. Independent studies injecting mouse eggs with human or mouse PAWP protein or cRNA failed to detect any Ca 2+ i transients (Nomikos et al 2014(Nomikos et al , 2015a).…”
Section: Pawp Is Not Relevant To Egg Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The oocyte-activating factors are transmitted from the sperm PT into the oocyte cytoplasm after the incorporation and rapid dissolution of the PT. In the normal fertilization cycle, the PT dissolves in the oocyte cytoplasm simultaneously with decondensation of the sperm nucleus and initiates division of the maternal pronucleus by hydrolyzing a membrane-bound phospholipid substrate, triggering cytoplasmic Ca 2+ oscillations [42]. In the case of ICSI, activation occurs only in the oocytes that contain a partly or completely dissolved PT.…”
Section: Perinuclear Thecamentioning
confidence: 99%